1994
DOI: 10.1002/chir.530060304
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐catalyzed stereoselective heteronucleophilic substitution and racemization of 3‐O‐methyloxazepam and 3‐O‐ethyloxazepam

Abstract: Enantiomers of 3-O-methyloxazepam (MeOX) and 3-O-ethyloxazepam (EtOX) were resolved by chiral stationary phase high-performance liquid chromatography (CSP-HPLC). Reaction kinetics and deuterium isotope effects of acid-catalyzed racemization of enantiomeric MeOX in ethanol and enantiomeric EtOX in methanol were studied by spectropolarimetry. The acid-catalyzed heteronucleophilic substitution reactions of racemic MeOX in ethanol and racemic EtOX in methanol were studied by reversed-phase HPLC. Thermodynamic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This situation was similar to those stereoselective homonucleophilic and heteronucleophilic substitution reactions studied earlier. 2,[4][5][6][9][10][11] We therefore propose that the mechanism involved in the acid-catalyzed stereoselective alcoholysis of TMZ enantiomers was the same as those involved in the Scheme 2. Proposed mechanism responsible for the racemization and stereoselective heteronucleophilic substitution of (R)-TMZ in anhydrous acidic alcoholic solvents.…”
Section: Mechanism Of Stereoselective Alcoholysis Of Tmzmentioning
confidence: 90%
See 1 more Smart Citation
“…This situation was similar to those stereoselective homonucleophilic and heteronucleophilic substitution reactions studied earlier. 2,[4][5][6][9][10][11] We therefore propose that the mechanism involved in the acid-catalyzed stereoselective alcoholysis of TMZ enantiomers was the same as those involved in the Scheme 2. Proposed mechanism responsible for the racemization and stereoselective heteronucleophilic substitution of (R)-TMZ in anhydrous acidic alcoholic solvents.…”
Section: Mechanism Of Stereoselective Alcoholysis Of Tmzmentioning
confidence: 90%
“…6 The K a values of rac-MeTMZ in MeOH and rac-EtTMZ in EtOH were 38 ± 3 (n = 3) and 110 ± 14 (n = 3) mM H 2 SO 4 , respectively. The K a values of rac-TMZ in MeOH and EtOH were 5.0 ± 0.5 and 15 ± 2 mM H 2 SO 4 , respectively.…”
Section: Acidity Constant By Spectrophotometrymentioning
confidence: 99%
“…Furthermore, they also suggested that racemization reaction occurred due to keto-enol tautomerism between C2 carbon of -CO group and C3 carbon; catalysed by a base. Similarly, Yang [25] reported acid catalyzed racemization of 3-O-methyloxazepam and 3-O-ethyl oxazepam in ethanol and methanol, respectively. These authors described a C3 carbocation intermediate as one of the most important steps in the racemization.…”
Section: In Vitro Racemizationmentioning
confidence: 95%
“…The chiral inversion of certain antiinflammatory drugs was reported as unidirectional in rat [112], rabbit and humans [113]. The important factors affecting racemization of these drugs were temperature, pH [25,28,[114][115][116][117][118] and organic solvent [25,28,[114][115][116]. In drug racemization and epimerization, the important action of human serum albumin (HSA) was also reported [106].…”
Section: Affect Of Variables On Racemizationmentioning
confidence: 96%
See 1 more Smart Citation